Effect of foliar application of elicitors on growth and yield of turmeric (Curcuma longa L.) (IASH Indian Journal of Arid Horticulture, 2026)
A field experiment was conducted during 2024-25 at farmer’s field to study the effect of foliar spray of elicitors on growth and yield of turmeric. The experiment was laid out in RBD with seven treatments replicated thrice. Application of salicylic acid (100 ppm) at 150, 180 and 210 days after planting (DAP), consistently produced maximum plant height (103.39 cm), number of leaves (15.82), leaf length (60.48 cm) and leaf width (16.24 cm). Yield attributes viz., total rhizomes (26.15), number and weight of mother rhizomes (2.95; 186.12 g), number and weight of primary rhizomes (10.12; 199.53 g), number and weight of secondary rhizomes (11.40; 58.07 g), yield per plant (443.72 g) and dry recovery (26.17%) were recorded highest with salicylic acid (100 ppm) sprayed at 150, 180 and 210 DAP. Therefore, salicylic acid at 100 ppm is recommended to improve growth and yield of turmeric.